Individual determinants of job-related learning and training activities of employees - An exploratory analysis of gender differences - Elisabeth Bublitz; Christina Boll (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Regarding gender differences, theory suggests that in a partnership the individual with the lower working hours and earnings position should exhibit lower training participation rates. Since women are more likely to match this description, we investigate whether systematic group differences explain gender variation. Across all countries, male workers are not affected by their earnings position. Disadvantages for female secondary earners arise only in Germany in the group of part-time workers when compared to single earners but not in the group of full-time workers. The findings hold at the extensive and the intensive margin, suggesting that, compared to the Netherlands and Italy, Germany faces particular obstacles regarding gender differences in job-related training.
Keywords: J16; J24; M53; 330